Strategi Pengelolaan Keuangan Syariah pada Masjid Nurul Jihad di Desa Kubangan Tompek - Yuris Asbi; Uswah Hasanah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to identify and analyze the strategies of Islamic financial management applied at Nurul Jihad Mosque, Kubangan Tompek Village, and measure the effectiveness of implementing Islamic financial principles in managing the mosque's finances. This research employs a qualitative approach with a case study method, where data is collected through in-depth interviews, direct observations, and document analysis. The findings reveal that Islamic financial management at Nurul Jihad Mosque is implemented through several key strategies, including transparent fund management, the use of Sharia-based accounting systems, and active community participation in fund collection and distribution. Additionally, the application of Islamic financial principles such as justice, transparency, and trustworthiness has proven to increase community trust in the mosque's fund management. The effectiveness of this financial management is indicated by increased donor participation, an increase in the amount of funds collected, and the appropriate allocation of funds. These findings provide important contributions to the development of an Islamic financial management model that can be adopted by other mosques to enhance transparency and accountability in fund management.